Transformational Leadership’s Impact On Employee Engagement: a Study of Formal Workers In Greater Jakarta - Andre Purnama Alam (Publikasiku, 2024)
This research analyzes the impact of Transformational Leadership on Employee Engagement. The data was collected from 119 workers who represented a population of formal workers in Greater Jakarta. Linear regression analysis were used to test hypothesis. The results show that Transformational Leadership has positive impact Employee Engagement. This finding provides further evidence for practitioners who aspire to get better employee performance through increasing Employee Engagement Level.